A Critical Analysis of Publications in The IJO Over 2006-15 - Shalini Gupta; A K Amitava (Delhi Journal of Ophthalmology)
Purpose: To qualitatively evaluate original articles in the IJO published over the decade from 2006 to 2015, using specific critical appraisal checklists (CACL), to assess whether publications have improved over time. Methods: All articles were classified either as systematic reviews/meta-analysis; randomised control trials; before and after studies; cohort studies; observational or descriptive and diagnostic test studies: and Economic analysis scored using CACLs. Scores were converted to percentages and compared between the earlier five years (E5Ys) and the later five (L5Ys). Annual trend in article counts and CACL scores were assessed. T-test and ANOVA, with significance set at p < 0.05 was used. 95% CIs are quoted. Results: Of a total of 529 original articles, there were 159 in the E5Ys, in 28 issues, while in the L5Ys; there were 370 articles in 48 issues. The mean score for E5Ys was 81.9±9.8% compared to 80.9±12.4% for L5Ys: p=0.26. Maximum articles (134) were in 2014. No significant trends in number and scores were observed. Conclusions: There were no significant qualitative differences in the quality of articles during the decade 2006 to 2015. Vitreoretinal subspecialty and observational studies formed the main bulk of articles published in the IJO during this decade. Systematic reviews and meta-analysis, considered the highest level of evidence, have scored the least on CACL.